Chronotope problem in gothic works - Sagidulliyeva, S.S.; Orazbek, M.S.; Sultangaliyeva, R.B. (Karagandy University of the name of acad. E.A. Buketov, 2023)
It is known that Gothic literature had previously become the object of study of many writers. The history of the formation and stages of the development of Gothic literature and plot specifics, chronotope, the way of transmitting characters and the system of motives, etc. were considered as an urgent problem of the study. Although the manifestation of Gothic elements was considered in English, European, Russian literature, the picture of the Gothic genre in Kazakh literature has not yet been considered to the fullest extent. In the works of writers of the period of independence, D. Kostolin, K. Mubarak, M. Omarova, M. Malik, A. Adilbek, national codes that reproduce our national knowledge, the suffix of folklore forgotten today, shaking consciousness are set forth. We analyze the works of the authors based on a small plot, a national worldview based on a new form, a formal search. The method of transmitting the Gothic style was analyzed, including the authors' consideration of the chronotopic situation. New practices of writers in providing time and space are considered.
Готикалық шығармалардағы хронотоп мəселесі
Проблема хронотопа в готических произведениях
Keywords: modern Kazakh literature; Gothic style; chronotope; literary process; national value; national code; national cognition; artistic solution; mysticism